MANAJEMEN PEMBELAJARAN TAHFIDZUL QUR’AN MELALUI PENDEKATAN LIVING QUR’AN ( Studi Multisitus di Pondok PesantrenMadrasatul Qur’an Tebuireng dan Pondok Pesantren Nurul Qur’an Bendungrejo Jogoroto Jombang ) - Moh. Jumali; Muhtadi; Adibah Jauhari (Arsy : Jurnal Studi Islam, 2018)
This research started from learning management tahfidzul qur’an in boarding school in environment MTs Madrasatul qur’an Tebuireng and MTs Nurul Qur’an Bendungrejo Jogoroto Jombang, Both of these institutions have manage tahfidzul qur an learning in boarding school starting from planning aspect, implementation and evaluation systemhe approach used is a qualitative approach with a multi-site study design. Data collection techniques are conducted by (I) in-depth interviews and (2) documentation Data analysis techniques include (1) data reduction (2) display data, and (3) Virtification, validation of findings is done using triangulation data.From the results of the study, the authors conclude that (1). In planning a Tahfidzul Qur'an learning program at MTs Madrasatul Qur'an and MTs Nurul Qur’an, it cannot be separated from the results of the meeting between units, namely the School Unit, Tahfidh Unit and MTT Unit (kepondokan). All units synergize in forming a pregnant person of the Qur'an lafdhan wa ma'nan and wa 'practice that is a person who brings the Qur'an / memorize the Qur'an, understands its meaning, is able to practice the contents of the contents and has akhlaqul karimah (2) behavior. The implementation of Tahfidzul Qur'an learning at MTs Madrasatul Qur’an and MTs Nurul Qur an is by coaching memorizing the Qur'an carried out 3 times a day with details of the dawn until 6:00 p.m. individual deposits until 16:30 p.m. and ba'da magrib until 7:30 p.m. fashohah (classical) for those who are still Bin-Nadhar and mudarosah together in the mosque for those who have tahfidh program (3) Evaluation System so that the memorization of al-Qur'an, besides being evaluated daily with rote deposit system, also held every three months held al-Qur'an memorization tests according to the number of opinions